Implementation of Hydrocarbon Teaching Materials Integrated with Spiritual Values Using the POGIL Model to Improve Learning Outcomes of Grade XI Students Viewed from Learning Interest - Intan Juwita; Ayi Darmana (Jurnal Pendidikan dan Pembelajaran Kimia, 2025)
Implementation of Hydrocarbon Teaching Materials Integrated with SpiritualValues Using the POGIL Model to Improve Learning Outcomes of Grade XI StudentsViewed from Learning Interest . This research aims to evaluate the effect of hydrocarbonteaching materials based on spiritual values on student learning outcomes, differences in spiritualattitudes before and after learning, and the effect of learning interest on learning outcomes. Thestudy used a quasi-experimental method with a quantitative approach and involved two randomlyselected classes. The instruments used included multiple-choice tests to evaluate learningoutcomes and non-test questionnaires to measure students' spiritual attitudes and learninginterests. Data analysis was carried out by testing normality, homogeneity, linearity, andhypothesis testing using independent t-tests, paired t-tests, and simple linear regression. Theresults showed that teaching materials based on spiritual values with the POGIL model had asignificant effect on student learning outcomes (sig. 0.001 ≤ α 0.05). There was a significantdifference in spiritual attitudes before and after learning (sig. 0.000 ≤ α 0.05). In addition, learninginterest influences learning outcomes, with a contribution of 25% in the experimental class (sig.0.002 ≤ α 0.05) and 39.4% in the control class (sig. 0.000 ≤ α 0.05).